PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP NEGERI 3 ONOLALU - Ternis Laia (Universitas Nias Raya, 2026)
The goals of this study are to (1) find out how the principal can help teachers perform better at SMP Negeri 3 Onolalu; and (2) find out how well teachers perform at SMP Negeri 3 Onolalu. Descriptive qualitative research is the focus of this kind of study. This examination was led from April 6 to May 14, 2024. Primary data are the sources of the data used in this study. Information assortment procedures utilized in this study are meetings, perceptions, and documentation. Information examination strategies utilized in this study are information decrease, information show, and reaching determinations. It is possible to draw the conclusion based on the findings of the research and discussion that the principal's role in enhancing teacher performance at SMP Negeri 3 Onolalu is significant. The principal serves as an educator and must encourage teachers to work toward enhancing learning. Additionally, the principal can conduct quarterly supervision or observation in the classroom, guide teachers, and grant permission to enhance training activities in the teacher certification program. As a result, it can be concluded that the principal's role in improving teacher performance at SMP Negeri 3 Onolalu as an educator must be fulfilled in order to enhance teacher learning. Every quarter, provide supervision and observation in the classroom. The idea in this review is that the chief ought to focus on tasks and think about working on the nature of training in the school climate by further developing ability and abilities and advancing to assist with further developing educator execution to acknowledge proficient instructors. For educators, they ought to continuously advance in improving and fostering the most recent learning models in executing the educational experience. for researchers who wish to investigate the same issues or variables in a variety of ways concerning the function of principal leadership and teacher performance.